PENDAMPINGAN PEMANFAATAN INTERNET SEHAT UNTUK ANAK SEKOLAH DASAR DI SD NEGERI 10 PALEMBANG - Fahreza; Irma Salamah; R.D.Kusumanto; Indah Putri Lestari; M.Munaza Fathsyah (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
The development of the internet has brought significant changes in all aspects of life. The internet can help human activities become easier, more effective and even more efficient both in terms of time and various other things. Improper use of the internet can have a significant negative impact. Students, especially the elementary school age category are very vulnerable to being exposed to unhealthy internet, due to their lack of knowledge of the internet and lack of understanding of the negative impacts that can be caused by the internet. This is due to the lack of education related to the internet to them. Therefore, how important is the role of parents, teachers, and the community in providing assistance, understanding, and education to elementary school children related to the internet. One solution that can be a solution to the problem above is the holding of Socialization / Counseling and Healthy Internet Training for Elementary School Children with the aim of providing understanding to elementary school children regarding healthy internet use and knowing what to do negative impact of internet use. Service activities in the form of socialization / counseling and healthy internet training obtained results and benefits including increasing sufficient understanding of the wise use of the internet so as to maximize the positive impact of the internet and minimize the negative impact of internet use, so as to create intelligent and productive children.